Getting-up rehabilitation therapy supported by movement based interaction techniques (2015)
Every day the number of diseases related to brain problems increases dramatically. Medical facilities are full of people who need complex rehabilitation processes as a result of suffering from Parkinson's disease, Alzheimer’s disease, brain stroke, or multiple sclerosis, as well as other conditions. Patients often spend a long time travelling every day to get to the corresponding rehabilitation clinics. Physiotherapists carefully attend patients over a period of time, and the exercises are often extremely repetitive. The type of patient suffering from these type of illnesses is unable to perform many common every day actions such as getting-up from a chair, walking in a straight line, picking up objects, etc. The system we propose in this paper provides a way for patients to perform the common rehabilitation process of gettingup from a chair. It monitors and guides the patient when the specialist considers they are prepared to do so. The specialists can focus on the results and the way to improve each rehabilitation process and not just on iterations.